Determinants of Success Candi Bumi Ayu Festival of Pali Regency - Muh. Yahyaddin, Muh. Yahyaddin; Muhammad Iqbal, Muhammad Iqbal; Handika Fikri Pratama, Handika Fikri Pratama; L. Suhairi Hazisma, L. Suhairi Hazisma; Ahmad Kurniawan, Ahmad Kurniawan; Rahmi Fadhela, Rahmi Fadhela; Ushy Ramadhanty, Ushy Ramadhanty (Journal of Tourism and Creativity, 2025)
The Candi Bumi Ayu Festival in PALI Regency is a cultural event aimed at preserving and promoting the local historical and cultural values. This study aims to analyze the impact of these factors on the success of the Candi Bumi Ayu Festival in PALI Regency. A quantitative approach was used, with a survey design and a sample of 300 respondents who were festival attendees. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS software. The results indicate that the quality of event management, effective marketing, government support, and community participation all have a positive and significant impact on the success of the festival. Support from local government is also a key factor, particularly in terms of funding and policy-making. Community participation, as a driving force behind the event, enriches the activities and creates a more vibrant atmosphere. This study provides recommendations for festival organizers to improve event management, strengthen marketing strategies, broaden government support, and encourage community participation for sustainable success.